Pengaruh Pendidikan, Kesehatan dan Inflasi Terhadap Kedalaman Kemiskinan di Indonesia - Hidayat, Ages Fitri; Amar, Syamsul (Universitas Negeri Padang, 2024)
This research aims to determine and analyze the influence of education, health and inflation on the depth of poverty in Indonesia. This research uses panel data from 2017 - 2021 in 34 provinces in Indonesia sourced from the Central Statistics Agency. Before using regression, the Chow test and Hausman test were carried out and the results of the analysis showed that the selected model was the Random Effect Model (REM). The research results reveal that: (1) Education has a significant effect on the depth of poverty in Indonesia (2) Health has an insignificant effect on the depth of poverty in Indonesia (3) Inflation has an insignificant effect on the depth of poverty in Indonesia. Based on the results of this research, it is recommended that the Government needs to expand learning opportunities and increase the allocation of boss funds. Then reduce inflation so that the poverty gap becomes narrower.